IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM PENINGKATAN HASIL BELAJAR SISWA DI MTsS HARAPAN BANGSA - Junias Zulfahmi; Cut Ismalia Benazir (Program Studi Manajemen Pendidikan Islam, 2022)
This study examines the implementation of MBS in improving student learning outcomes at MTsS Harapan Bangsa Aceh Barat, intending to determine: 1) MBS planning in improving student learning outcomes. 2) Implementation of MBS in improving student learning outcomes, and 3) Supporting factors for the implementation of MBS in improving student learning outcomes in MTsS Harapan Bangsa. This research uses qualitative descriptive methods with data collection techniques by observation, interviews, and documentation. The subjects in this study were the head of the madrasah, the head of the TU, and the teacher. The results of this study show that the implementation of MBS, especially the management of educators and education personnel in improving student learning outcomes, is first carried out planning in the form of needs analysis, recruitment and placement, compensation, coaching and development, and conducting evaluations. Concerning improving student learning outcomes, through the implementation of MBS, teachers can act autonomously by developing varied approaches, strategies, media, and teaching methods to motivate students to follow the learning process so that their learning outcomes increase. Meanwhile, the supporting factors for the implementation of MBS are the leadership of the head of the madrasah who is professional, social conditions, and public appreciation of education as well as government support for education.